RELATIONSHIP BETWEEN ESTIMATED AVERAGE GLUCOSE AND GLYCATED HEMOGLOBIN - Khan, Sikandar Hayat; Fazal, Nadeem; Gilani, Athar Abbas Shah; Asif, Naveed; Ijaz, Amir; Manzoor, Syed Mohsin; Yasir, Muhammad; Niazi, Najam Saquib Khan (Journal of Postgraduate Medical Institute, 2018)
Objective: To correlate estimated average glucose (eAG) with glycated hemoglobin (HbA1c) among patients referred from medical and surgical OPDs. Methodology: This cross-sectional study was carried out between January 2016 to July 2017 at the Department of Pathology and Medicine, PNS HAFEEZ Hospital, in collaboration with Department of Chemical Pathology, AFIP. A total of 110 males and 122 females were finally selected for inclusion in the study. They were sampled for fasting plasma glucose, HbA1c and insulin levels. Estimated average glucose (eAG) was calculated as per A1c derived average glucose (ADAG) formula; while insulin resistance was calculated as per the recommendations of Matthew's et al. Results: Pearson's correlation measured between eAG with age, fasting plasma glucose (FPG) and HbA1c were as: [Age: r =0.032 (p =0.629)], [FPG: r =0.547 (p <0.001)], [HOMA-IR: r =0.259 (p <0.001)]. The comparison of various groups based upon FPG results, eAG derived from ADAG equation depicted an increasing trend from group-1 to group-4 as: Group-1 (n =117): [6.17 (95% CI: 5.92- 6.42)], to group-2 (n =45): [6.36 (95% CI: 6.02-6.70) ], to group-3 (n =43): [6.79 (95% CI: 6.41-7.18)], to group-4 (n =23): [8.66 (95% CI: 7.61-9.70)], (p <0.001). Conclusion: Estimated average glucose (eAG) utilizing HbA1c demonstrated significant positive correlation with fasting plasma glucose.